Social complexity and team cohesion in multiparty information systems development projects. (15th May 2018) - McCarthy, Stephen; O'Raghallaigh, Paidi; Fitzgerald, Ciara; Adam, Frédéric
Abstract: Despite the proliferation of Critical Success Factors (CSFs) for Information Systems Development (ISD), the rate of ISD project failure continues to remain exorbitantly high. In particular, social complexity is increasingly seen as an innate feature of multiparty ISD projects which make them less amenable to being 'tamed'. However, an understanding of the intricacies of social complexity and how it impacts team cohesion in multiparty projects remains nascent. In this paper we offer findings from the case study of a funded academia-industry collaboration to investigate the elusive phenomenon of social complexity. A theoretical framework is developed to reveal the factors which contribute to social complexity and its impact on team cohesion in multiparty ISD projects. The findings derived from the application of this lens reveal the numerous challenges to team cohesion that arose from the interplay between macro- and micro-level factors. Theoretical and practical implications from the paper are also outlined.